Data base of Benefits of Hydrotherapy in patients with chronic obstructive pulmonary disease: additional results from a randomized controlled trial - Gallo-Silva, Bruna (2025)
The objective of this article was to assess the effect of hydrotherapy on the functional status, dyspnea, BODE index, and quality of life in patients with COPD. Randomized, controlled clinical trial consisting of 24 patients with COPD randomly divided into two groups: 1) aquatic training group (ATG), participating in an intermittent aquatic training (AT) program in a moderate/high intensity three times a week, for 8 weeks; 2) control group (CG), which received guidance on healthy lifestyle and not supervised exercises. The variables functional status, dyspnea, BODE index, and quality of life were assessed before and after the intervention period. The level of significance was established in 5%. Results shows that the ATG presented significant improvement in the activity of daily living (LCADL total Δscore: -10.1, p=0.01), in the functional status (PFSDQ-M, total Δscore: -16.9, p=0.01), dyspnea (ΔMRC: -1.37, p=0.003), BODE index (Δ: -1.25, p=0.048) and quality of life (total Δscore: -7.4, p=0.02). Similar changes were not observed in the CG. As a conclusion, the intermittent aquatic aerobic training of moderate/high intensity promoted a significant and clinically relevant improvement for most patients with COPD in their quality of life, in the limitations of their activities of daily living, dyspnea, and in the BODE mortality predictor index.